(untitled) (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the constitutional limits of budget-efficiency policy after Presidential Instruction Number 1 of 2025, especially where government discretion intersects with the protection of public services. The issue arises because efficiency is a lawful principle of state-finance management, yet education and health are also tied to constitutional guarantees, statutory duties, and minimum service standards. Using normative legal research with statutory, conceptual, and limited case approaches, this article analyses the relationship between the 2025 efficiency instruction, the State Finance Law, the 2025 State Budget Law, the education budget jurisprudence of the Constitutional Court, and the statutory framework on basic public services. The article argues that post-Inpres efficiency remains lawful only if it is directed at measurable non-core spending, does not erode constitutional spending floors and minimum service obligations, and is documented through a transparent service-protection test.